Media Interaktif Sebagai Solusi Inovatif Pembelajaran Ipa Dan Matematika Di Era Digital - Elia Putri; Amanda Syahri Nasution; Sutri Novika; Nova Zulfani Panggabean; Yulia Lestari (Amaliah: Jurnal Pengabdian Kepada Masyarakat, 2025)
The development of digital technology demands an increase in teacher competence in integrating interactive media in the learning process, especially science and mathematics subjects that are often considered difficult by students. The main problem faced by junior high school teachers in Pasar Dua Patumbak Patumbak District Deli Serdang Regency is the limitation in utilizing digital learning media that is interesting and effective. This service activity aims to improve the ability of teachers to design and use digital-based interactive media to support innovative and fun learning. The implementation method includes training, mentoring and hands-on practice of making learning media using simple applications such as Canva, interactive PowerPoint, and Wordwall. The results of the activity showed a significant increase in teacher competence as shown by the evaluation results before and after the training where 85% of teachers experienced an increase in understanding in the use of interactive media and 78% succeeded in making media that was feasible to be applied in the classroom. 82% of teachers felt more confident to be able to apply interactive media in science and mathematics learning. The results of these activities show that structured and practical interactive media training is proven to be effective in improving the quality of teacher teaching and can be an innovative solution for learning in the digital era.